Task and socioemotional behaviors of physicians: a test of reciprocity and social interaction theories in analogue physician–patient encounters - Roberts, Carlos A; Aruguete, Mara S (Social science & medicine (1982), 2000)
The purpose of the present study is to assess social interaction and reciprocity theories as explanations for patient responses to a physician in a medical consultation. Social interaction theory predicts that patients mostly recognize and react to socioemotional behavior of their physicians due to a lack of understanding of physician task behaviors or a preoccupation with anxiety. Reciprocity theory predicts that patients recognize socioemotional and task behaviors of their physicians, and they respond to these behaviors in thematically similar ways. We examined these hypotheses by having subjects view one of four videotapes which varied in physician task behavior (thorough or minimum levels of explanation of etiology, symptoms, and treatment) and physician socioemotional behavior (high or low levels of concern and affection displayed verbally and non-verbally). Results supported the general proposition of social interaction theory in that high levels of socioemotional behavior of the physician increased measures of patient self-disclosure, trust, satisfaction, and likelihood of recommending the physician. Physician task behavior had no effect on patient response to the physician, a finding inconsistent with reciprocity theory.